Study on the Upgrading Citronella (Cymbopogon nardus L.) Oil Isolation Using Microwave Assisted Hydro-distillation Method - Diana Diana; Venitalitya Alethea Sari Augustia; Arif Hidayat; Kiki Adi Kurnia (Jurnal Kimia Sains dan Aplikasi, 2024)
Isolation of essential oil using microwave-assisted hydro-distillation (MAHD) method could enhance the yield compared to steam-distillation or conventional hydro-distillation methods. This study explored the isolation of essential oil from Citronella (Cymbopogon nardus L.) using the MAHD method with several parameters, such as solid-to-liquid ratio, power of the microwave, and extraction time. The essential oils produced were evaluated based on yield, density, refractive index, and composition. The result showed that the density of the essential oil product was in the range of 0.866–0.902 g/mL, while the refractive index was in the range of 1.470–1.475, which met the ISO standard. Chemical compounds were identified using Gas Chromatography-Mass Spectrometry (GC-MS) analysis. It was found that the total amount of citronellal, citronellol, and geraniol in the product obtained by MAHD is higher than the one from conventional methods. This study aims to identify the most efficient operating conditions to maximize yield while analyzing energy consumption to determine the most cost-effective conditions.